Optimalisasi Aplikasi VR Mahakarya Vokasi Land Menggunakan Teknik Level of Detail (LOD) - Riwinoto Riwinoto; Cikal Lisandi Putra (Politeknik Negeri Batam, 2023)
The development of the VR exhibition application for mahakarya vokasi Land using Level of Detail (LOD) is the focus of this research. LOD allows for adjusting the detail of 3D objects based on the user's viewing distance, reducing computational load, and improving application performance. LOD Groups are used to categorize objects based on complexity levels and dynamically adjust the level of detail. The research results indicate that the use of LOD successfully increased FPS by 284% and reduced memory usage in several important parameters such as setPass Calls, draw calls, batches, triangles, vertices, used textures, render textures, and shadow casters. Although some parameters did not show a significant improvement in FPS, it is important to monitor and optimize them. The use of LOD can be an effective strategy to improve the performance of VR exhibition applications by reducing rendering and memory load, creating a smoother and more responsive VR experience